2020
DOI: 10.1039/c9ra10020b
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin, a citrus polymethoxyflavone, enhances the effects of bicalutamide on prostate cancer cellsviadown regulation of NF-κB, STAT3, and ERK activation

Abstract: Nobiletin enhance the anticancer effect of bicalutamide on prostate cancer cells via down regulation of NF-κB, STAT3, Erk activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In hepatocellular carcinoma cells, hesperetin induces the activation of apoptosis-inducing factors by mediating the excessive production of intracellular ROS and increasing Ca 2+ levels [ 34 ]. Nobiletin, a polymethoxyflavone present in citrus fruits, has a synergistic effect in inhibiting colony formation and inducing apoptosis of prostate cancer cells when combined with anti-androgen drugs used for prostate cancer therapy [ 35 ]. Hesperidin is also a major compound found in citrus fruits and is well known for its wide range of pharmacological effects, such as anti-inflammatory, anti-allergic, and anti-viral effects [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma cells, hesperetin induces the activation of apoptosis-inducing factors by mediating the excessive production of intracellular ROS and increasing Ca 2+ levels [ 34 ]. Nobiletin, a polymethoxyflavone present in citrus fruits, has a synergistic effect in inhibiting colony formation and inducing apoptosis of prostate cancer cells when combined with anti-androgen drugs used for prostate cancer therapy [ 35 ]. Hesperidin is also a major compound found in citrus fruits and is well known for its wide range of pharmacological effects, such as anti-inflammatory, anti-allergic, and anti-viral effects [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…PMFs, especially nobiletin, have been combined with other anti-cancer agents to fight against cancer in vitro and in vivo. Cell-based assays suggested that nobiletin enhanced the anti-cancer abilities of imatinib and bicalutamide against chronic myeloid leukaemia cells [60] and prostate cancer cells [72] ,…”
Section: Synergistic Anti-cancer Effects With Other Agentsmentioning
confidence: 99%
“…Polymethoxylated flavones have been highlighted for their anti-inflammation [30] and anticancer effects [31] in recent years. However, the effects of nobiletin and tangeretin on eNOS expression in human endothelial cells have not been investigated.…”
Section: Differential Effects Of Citrus Flavonoids On Enos Expressionmentioning
confidence: 99%